Wave transformation across a macrotidal shore platform under low to moderate energy conditions. Issue 1 (6th October 2017) - Stephenson, Wayne J.; Naylor, Larissa A.; Smith, Helen; Chen, Bin; Brayne, Ralph P.
Abstract: We investigate how waves are transformed across a shore platform as this is a central question in rock coast geomorphology. We present results from deployment of three pressure transducers over four days, across a sloping, wide (~200 m) cliff‐backed shore platform in a macrotidal setting, in South Wales, United Kingdom. Cross‐shore variations in wave heights were evident under the predominantly low to moderate (significant wave height < 1.4 m) energy conditions measured. At the outer transducer 50 m from the seaward edge of the platform (163 m from the cliff) high tide water depths were 8+ m meaning that waves crossed the shore platform without breaking. At the mid‐platform position water depth was 5 m. Water depth at the inner transducer (6 m from the cliff platform junction) at high tide was 1.4 m. This shallow water depth forced wave breaking, thereby limiting wave heights on the inner platform. Maximum wave height at the middle and inner transducers were 2.41 and 2.39 m, respectively, and significant wave height 1.35 m and 1.34 m, respectively. Inner platform high tide wave heights were generally larger where energy was up to 335% greater than near the seaward edge where waves were smaller. Infragravity energy was less than 13% of the total energy spectra with energy in the swell, wind and capillary frequencies accounting for 87% of the total energy. Wave transformation is thus spatially variable and is strongly modulated by platform elevation and the tidal range. While shore platforms in microtidal environments have been shown to be highly dissipative, in this macro‐tidal setting up to 90% of the offshore wave energy reached the landward cliff at high tide, so that the shore platform cliff is much more reflective. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : We investigate how waves are transformed across a shore platform as this is a central question in rock coast geomorphology. In this macro‐tidal setting, under the wave conditions measured, up to 90% of the offshore wave energy reached the landward cliff at high tide, so that the shore platform cliff is highly reflective. At high tide inner platform wave heights were generally larger than near the seaward edge and infragravity energy was less than 13% of the total energy spectra.